Antecipação de nitrogênio para a cultura do milho em sucessão a gramíneas forrageiras no sistema plantio direto - Marques, Letusa Momesso [UNESP] (2015)
Currently, the recommendation of nitrogen fertilization for corn (Zea mays) in no-tillage system in Brazil is carried out based on the concept of expected yield. The possibility of new alternatives has emerged for management of nitrogen fertilization on these systems. Some farmers are applying all nitrogen (N) in advance to the straw producing crop or on the straw on the eve of sowing the maize crop. The objective of this study was to verify the technical viability of this practice, in no-tillage system. The experiment was evaluated for three crop years (2011/12, 2012/13 and 2014/15), at Lageado Experimental Farm, Faculty of Agricultural Sciences - UNESP, Botucatu, SP, Brazil. The experimental design was a randomized block with four replications, in factorial 2x6. The treatments were a combination of cover crops Urochloa brizantha or U. ruziziensis, with six forms of management of nitrogen fertilization: 0 kg ha-1 N (control); three managements anticipated in the cover crops (20, 10 and 5 days before desiccation); pre-sowing (1 day before) at a dose of 200 kg ha-1 N; and conventional application in maize (30 and 170 kg ha-1, at seeding and sidedressed at the four leaf stage, respectively). The following evaluations were performed on forage plants: dry matter mass yield and accumulated amount of macronutrients, an the corn crop were determined dry matter of shoots, leaf analysis, plant height, yield components and grain yield. The application of N before the desiccation of cover crops, increased dry matter yield and the accumulation of macronutrients, mainly for Urochloa brizantha. Regardless of the management of nitrogen, there was an increase in the number of ears per plant, grain per spike, the mass of one hundred grains and productivity of grains in succession to Urochloa brizantha. It was feasible to anticipate the application of N at ...